Ceramic modified acid scavenging polyolefin membranes

By distributing hydrotalcite particles in the polyolefin film of the lithium-ion battery separator or using them as a surface coating, the problem of dimensional instability of the separator at high temperature and insufficient acid removal ability is solved, high temperature dimensional stability and acid removal ability are achieved, and the safety and performance of the battery are improved.

CN119547265APending Publication Date: 2025-02-28AMTEK RESEARCH INTERNATIONAL LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380053009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-08-01
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are unstable in size at high temperatures and are difficult to achieve acid removal capabilities, which affects the cycle life and performance of the battery.

Method used

Hydral talc particles are synthesized in the bulk structure of the polyolefin film or used as a surface coating, combined with other inorganic particles, to form a microporous polyolefin film with high temperature dimensional stability and acid removal ability.

Benefits of technology

The high-temperature dimensional stability and acid removal capability of the film at high temperatures are achieved, and the safety and performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547265A_ABST
    Figure CN119547265A_ABST
Patent Text Reader

Abstract

The present disclosure relates to the formation of stand-alone microporous polyolefin films that exhibit both high temperature dimensional stability and acid scavenging capabilities. Such films may comprise hydrotalcite particles, which may contribute to high temperature dimensional stability and acid scavenging. Such membranes may be used to improve manufacturability, performance (e.g., cycle life), and safety of energy storage devices such as lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 370,214, filed on August 2, 2022, and entitled CERAMIC-MODIFIED, ACID-SCAVENGING POLYOLEFIN SEPARATORS, which is incorporated herein by reference in its entirety.

[0003] Copyright Notice

[0004] ©2023 Amtek Research International LLC. A portion of the disclosure of this patent document contains material that is subject to copyright protection. The copyright owner has no objection to the facsimile reproduction by anyone of the patent document or the patent disclosure, as it appears in the Patent and Trademark Office patent files or records, but otherwise reserves all copyright rights whatsoever. 37 CFR §1.71(d). Technical Field

[0005] The present disclosure relates to the formation of freestanding microporous polyolefin membranes modified with a mixture of inorganic particles within their bulk structure or on at least one surface such that the inorganic particles provide both high temperature dimensional stability and acid scavenging capability. These membranes exhibit (1) in-plane high temperature dimensional stability (i.e., low shrinkage (e.g., less than 10% shrinkage)) at temperatures both above and below the melting point of the polymer matrix of the polyolefin membrane, and (2) exhibit the ability to scavenge acids via an anion exchange mechanism. At high temperatures (>135°C), pores within the bulk structure may begin to collapse or close, thereby changing the permeability through the membrane with little in-plane dimensional change. Such membranes can be used to improve the manufacturability, performance (e.g., cycle life), and safety of energy storage devices such as lithium-ion batteries. Background Art

[0006] The separator is an integral part of the performance, safety and cost of lithium-ion batteries and rechargeable Li metal batteries. During normal operation, the main function of the separator is to prevent electronic conduction (i.e., short circuit or direct contact) between the anode and the cathode while allowing ionic conduction via the electrolyte. For small commercial battery cells under abuse conditions (such as external short circuit or overcharge), the separator is required to be closed at a temperature far below that at which thermal runaway may occur. Closure is caused by the collapse of pores in the separator due to the melting and viscous flow of the polymer, thereby slowing down or preventing the flow of ions between the electrodes. Almost all Li-ion battery separators contain polyethylene as part of a single or multilayer construction, so that closure begins at about 130°C (i.e., close to the melting point of polyethylene).

[0007] Separators for the lithium-ion market are currently manufactured via either a "dry" or "wet" process. Celgard LLC and others have described a dry process in which polypropylene (PP) or polyethylene (PE) is extruded into a thin sheet and subjected to rapid drawing. The sheet is then annealed at 10°C-25°C below the melting point of the polymer so that the crystallite size and orientation are controlled. Next, the sheet is rapidly stretched in the machine direction (MD) to achieve slit-like pores or voids. Three-layer PP / PE / PP separators have anisotropic mechanical properties and are difficult to manufacture at high yields at thicknesses of ≤14um, thereby limiting the volumetric energy density of lithium-ion battery cells.

[0008] The wet process diaphragm consisting of high molecular weight polyethylene is produced by extruding a plasticizer / polymer mixture at an elevated temperature, followed by phase separation, biaxial stretching, and extraction of a pore former (i.e., a plasticizer). The resulting diaphragm has an elliptical or spherical hole, which has good mechanical properties in both the machine direction and the transverse direction. The diaphragm based on PE manufactured in this way by Toray, SEM Corp., Shenzhen Senior, W-Scope, Asahi-Kasei, SKIET, and ENTEK has been widely used in Li-ion batteries. Wet process diaphragms can be easily produced with a thickness ranging from 5 to 12 um, and they are preferred choices for OEMs manufacturing Li-ion batteries for electric vehicles.

[0009] In the case of large format Li-ion cells or rechargeable Li metal cells designed for electric vehicle applications, the benefits of membrane closure have been openly questioned because of the difficulty in ensuring adequate rate and uniformity of closure throughout the cell. As such, many companies have focused on changing the construction of lithium-ion batteries to include (1) a heat-resistant separator or (2) a heat-resistant layer coated on either electrode of a conventional polyolefin separator. These approaches are designed to prevent oxidation of the polyolefin surface in high voltage cells and minimize in-plane separator shrinkage so that the edges of the current collectors cannot contact each other, thereby reducing the possibility of short circuits and thermal runaway.

[0010] In U.S. Pat. No. 9,896,555 B2, Pekala et al. demonstrated a free-standing microporous ultra-high molecular weight polyethylene (UHMWPE)-based separator containing sufficient inorganic filler particles distributed throughout the polymer matrix (bulk structure) to provide low shrinkage while maintaining high porosity at temperatures above the melting point of the polymer matrix (>135° C.) Such free-standing heat-resistant separators have excellent wettability and ultra-low impedance, but they may not exhibit closed-cell properties due to the high loading level of the inorganic filler.

[0011] OEM battery cell manufacturers ideally want a separator that has (1) high temperature dimensional stability and (2) still exhibits closed-cell characteristics. To meet this demanding requirement, the PE separator is coated on one or both sides with a heat-resistant inorganic (ceramic) layer. Boehmite and alumina are the two most commonly used ceramics in the coating process, and in some cases, poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) or acrylates are blended with ceramics to promote adhesion to the electrode. The main advantage of ceramic-coated PE separators is that they can still exhibit closed pores in the thickness direction, while sufficient ceramic coating produces excellent high temperature dimensional stability (<5% in-plane shrinkage) at 180°C, which is about 50°C above the melting point of polyethylene.

[0012] In U.S. Pat. No. 7,638,230B2, a porous heat-resistant layer is applied to the negative electrode. The heat-resistant layer is composed of an inorganic filler and a polymer binder. The inorganic filler includes magnesium oxide, titanium dioxide, zirconium oxide, or silicon dioxide. The polymer binder includes a modified rubber mixture of polyvinylidene fluoride and acrylonitrile units. The heat-resistant layer contains 1-5 parts of binder per 100 parts by weight of inorganic filler. Higher binder content will negatively affect the high rate discharge characteristics of the battery. In addition, the thickness of the porous heat-resistant layer must be limited to 1-10um to obtain a high discharge rate, and it cannot be removed as a free-standing film. Free-standing means that the sheet has sufficient mechanical properties to wind or unwind an unsupported web.

[0013] In U.S. Patent Application Publication No. 2008 / 0292968A1 and U.S. Patent Application Publication No. 2009 / 0111025A1, an organic / inorganic separator is disclosed, wherein a porous substrate is coated with a mixture of inorganic particles and a polymer binder to form an active layer on at least one surface of the porous substrate. The porous substrate can be a nonwoven fabric, a film, or a polyolefin-based separator. The inorganic particles are selected from the group consisting of those exhibiting a dielectric constant greater than 5, piezoelectricity, and / or lithium ion conductivity. A variety of polymer binders are described. Compared with uncoated polyolefin-based separators used in Li-ion batteries, the composite separator is said to show excellent thermal safety, dimensional stability, electrochemical safety, and lithium ion conductivity. In the case of certain polymer binders mixed with inorganic particles, the electrolyte may cause a high degree of swelling in the surface layer, but rapid wetting or swelling is not achieved in the polyolefin substrate.

[0014] In the latter method, there is an inorganic layer that is applied to the surface of the electrode or porous substrate in a secondary coating operation to provide heat resistance and prevent internal short circuits in the battery. To date, it has not been considered to impart acid scavenging capabilities to inorganic particles to improve the cycle life and performance of lithium-ion batteries. Although U.S. Pat. No. 10,050,313 B2 and U.S. Pat. No. 10,741,812 B2 discuss organic chelating agents or nitrogen-containing polymers that can be coated on at least one surface of a polyolefin separator for acid scavenging or distributed throughout its bulk structure, these methods do not impart high temperature dimensional stability to the separator.

[0015] Thus, it is necessary to develop a ceramic modified separator that can provide both high temperature dimensional stability and acid scavenging ability to improve the safety and performance of lithium ion batteries or rechargeable Li metal batteries. In the present disclosure, synthetic hydrotalcite is used as inorganic particles, which can simultaneously contribute to high temperature dimensional stability and acid scavenging. Summary of the invention

[0016] The purpose of this disclosure is to realize the thin independent microporous polyolefin membrane with excellent high temperature dimensional stability and acid scavenging ability by incorporating the inorganic particles distributed throughout the polymer matrix of the bulk structure or as a surface coating.Synthetic hydrotalcite has been identified as the inorganic particles that can give the above characteristics.This type of particle can be used alone or in combination with other inorganic or organic particles to produce desired polyolefin membrane.This type of polyolefin membrane can be used to form an effective separator for energy storage devices such as lithium ion batteries.

[0017] As used herein, freestanding may refer to a film having sufficient mechanical properties for use in an energy storage device assembly, which properties allow operations such as winding and unwinding in the form of a film. Throughout this patent application, the terms film, thin film, and sheet may be used interchangeably to describe products manufactured according to the disclosed embodiments, and the term film may be used to encompass webs, thin films, and sheets.

[0018] In the first embodiment of the present disclosure, the microporous polyolefin membrane is passed through an aqueous dispersion of hydrotalcite particles containing a small percentage of a polymer binder so that an inorganic layer with controlled thickness is deposited on one or both of the first and second main surfaces. Gravure printing, microgravure printing, slot die, dip coating, direct metering or other methods can be used to control the thickness of the surface coating. Subsequently, the wetted film is dried, such as dried in an oven with a series of air knives, and hot air is used in the oven to evaporate the solvent. The coated film is then wound into a master roll, which can be used to form a battery separator later.

[0019] In a second embodiment of the present disclosure, a microporous polyolefin membrane is passed through an aqueous dispersion containing hydrotalcite particles, at least one other type of inorganic particles (e.g., fumed alumina, boehmite, or a mixture thereof) and a small percentage of a polymer binder so that an inorganic layer with a controlled thickness is deposited on one or both of the first and second main surfaces. For example, the inorganic particles in the aqueous dispersion can include about 0.1%-12% of hydrotalcite particles and about 88%-99.9% of at least one other type of inorganic particles. The thickness of the surface coating can be controlled using gravure printing, micro-gravure printing, slot die, dip coating, direct metering or other methods. The wetted film is then dried, such as by drying in an oven with a series of air knives, in which hot air is used to evaporate the solvent. In this case, the surface layer contains a mixture of inorganic particles, all of which contribute to high temperature dimensional stability, but only hydrotalcite has the ability to act as an acid scavenger through anion exchange.

[0020] In the third embodiment of the present disclosure, a microporous free-standing polyolefin membrane is manufactured by combining polyethylene (e.g., VHMWPE-very high molecular weight polyethylene), hydrotalcite particles (or a mixture of hydrotalcite particles and at least one other type of inorganic particles) and a plasticizer (e.g., mineral oil). For example, a dry blend of polyethylene powder and hydrotalcite particles (or a mixture of hydrotalcite particles and at least one other type of inorganic particles) is combined with a plasticizer and extruded into a uniform viscous material having hydrotalcite particles (or a mixture of hydrotalcite particles and at least one other type of inorganic particles) distributed throughout it. The material is processed using a blown film, cast film or calendering method to obtain an oil-filled sheet that leaves the die and can be further biaxially oriented to reduce its thickness and affect its mechanical properties. In an extraction operation, the oil is removed with a solvent, and the solvent is subsequently evaporated to produce a microporous free-standing membrane containing hydrotalcite particles (or a mixture of hydrotalcite particles and at least one other type of inorganic particles) distributed within and throughout the bulk matrix. For example, the microporous membrane may contain from about 0.1 wt % to about 80 wt % of hydrotalcite particles (or a mixture of hydrotalcite particles and at least one other type of inorganic particle). Optionally, the hydrotalcite-containing membrane may be subsequently coated with at least one other type of inorganic particle (e.g., fumed alumina, boehmite, or a mixture thereof) at a coating weight sufficient to impart good high temperature dimensional stability.

[0021] In a fourth embodiment, one of the above manufacturing methods is used to produce a microporous freestanding membrane containing at least one type of inorganic particles (e.g., fumed alumina, boehmite, or a mixture thereof) in the bulk structure. Optionally, the microporous membrane is subsequently coated with a surface layer containing hydrotalcite at a coating weight sufficient to impart good high temperature stability. The surface layer containing hydrotalcite may contain only hydrotalcite particles as inorganic particles, or a mixture of hydrotalcite particles and at least one other type of inorganic particles as inorganic particles.

[0022] The above microporous free-standing polyolefin membranes can be wound or stacked in packaging to separate electrodes in energy storage devices (e.g., batteries, capacitors, supercapacitors, or fuel cell units). The membrane pores can be filled with electrolyte in the surface layer and throughout the inorganic modified bulk structure. Such membranes are beneficial for the manufacture of energy storage devices, particularly because they combine good heat resistance, in-plane dimensional stability, acid scavenging ability, and closed-cell characteristics.

[0023] Additional objects and advantages of the present disclosure will become apparent from the following detailed description of preferred embodiments thereof, which proceeds with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1A titration curve showing the titration of a hydrotalcite dispersion with concentrated HCl is depicted.

[0025] Figures 2A-2D Vials demonstrating the effect of hydrotalcite on electrolyte degradation compared to control vials are described. DETAILED DESCRIPTION

[0026] The film used in the present disclosure is composed of a polyolefin matrix. The type of polyolefin and its molecular weight generally depend on the manufacturing method (e.g., blown film vs. cast film). In the blown film method, the polyolefin most preferably used is an ultra-high molecular weight polyethylene (UHMWPE) with an intrinsic viscosity of at least 10 deciliters / gram and preferably in the range of 18-22 deciliters / gram. The molecular weight of UHMWPE generally corresponds to a range between about 3.10 and about 10 million grams / mole. It may be desirable to blend UHMWPE with other polyolefins such as HDPE or linear low density polyethylene (LLDPE) in order to affect the closed-cell properties of the film. In the case of cast film, the polyolefin most preferably used is a high-density polyethylene (VHMW-HDPE) with a very high molecular weight of about 600,000 to about 1.5 million grams / mole.

[0027] The plasticizer used in the present disclosure is a non-evaporating solvent for the polyolefin polymer and is preferably liquid at room temperature. The plasticizer has little or no solvating effect on the polymer at room temperature; it exerts its solvating effect at or above the softening temperature of the polymer. For UHMWPE, the solvating temperature will be above about 160°C, and preferably in the range of between about 160°C and about 220°C. It is preferred to use a process oil, such as a paraffinic oil, a naphthenic oil, an aromatic oil, or a mixture of two or more such oils. Examples of suitable process oils include: oils sold by Shell Oil Company, such as 430X; and oils sold by Calumet Lubricants, such as Hydrocal TM 800; and oils marketed by Nynas Inc., such as 330.

[0028] The polymer / oil mixture is extruded through a sheet die or an annular die, and then biaxially oriented to form a thin oil-filled sheet. A solvent miscible with oil can be used for the extraction step, provided that the boiling point of the solvent makes it practical to dry and separate the solvent from the plasticizer by distillation. Exemplary solvents include 1,1,2 trichloroethylene, perchloroethylene, 1,2-dichloroethane, 1,1,1-trichloroethane, 1,1,2-trichloroethane, methylene chloride, 1,1,2-trichloro-1,2,2-trifluoroethane, various trans-dichloroethylene azeotropes (e.g., Tergo MCF-MicroCare LLC), isoPar-G, hexane, heptane, and toluene. In some cases, it is desirable to select a processing oil so that any residual oil in the polymer sheet after extraction is electrochemically inactive. The resulting polyolefin film after extraction is microporous with a porosity of about 35%-65%. The pore size range is typically from about 10 nanometers to several micrometers, with the average pore size being less than about 1 micrometer. The thickness of the polyolefin membrane may be in the range of about 3-25 μm.

[0029] The coating formulation used in the present disclosure is composed of inorganic particles dispersed in an aqueous mixture, and these aqueous mixtures can contain a small amount of alcohol to improve the wettability of the polyolefin film surface. The inorganic particles are typically charge-stabilized and remain suspended in the aqueous mixture. Polymer dispersions or water-soluble polymers are typically used as adhesives for inorganic particles. It is desirable to select a polymer with hydrogen bonding sites so that the adhesive concentration is minimized, but to achieve a robust microporous surface layer that is not easy to fall off the inorganic particles. Acrylate, polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose and copolymers or derivatives thereof are preferred polymer adhesives, so that a polymer adhesive less than or equal to 10 parts can be used with 90 parts or more of inorganic particles.

[0030] In the case of Li-ion or rechargeable Li metal batteries, the electrolyte is typically composed of 1-1.2M LiPF6 (lithium hexafluorophosphate) dissolved in a mixture of organic carbonates (e.g., dimethyl carbonate (DMC), ethyl methyl carbonate (EMC)). This lithium salt is highly reactive with water, so that hydrofluoric acid (HF) can be easily generated within the electrochemical cell. The presence of hydrofluoric acid accelerates other parasitic reactions (e.g., transition metal dissolution from the cathode active material) that negatively affect the cycle life and performance of the Li-ion battery. Although fumed alumina, boehmite, and other inorganic oxides can often adsorb hydrofluoric acid to their surfaces, they do not have an ion exchange mechanism that locks the halogen anions within the interlayer regions of the hydrotalcite.

[0031] Hydrotalcites have a layered structure consisting of magnesium oxide and aluminum oxide. They are considered layered double hydroxides, an unusual class of layered materials that have positively charged hydroxide layers and charge-balancing mobile anions located in the interlayer regions. These hydrotalcites can be used as acid scavengers.

[0032] Although hydrotalcites are anionic clays that can be found in nature, they are available in high purity synthetic form from companies such as Kisuma Americas, Inc (Houston, TX). These high purity synthetic hydrotalcites are perhaps of most interest for Li-ion batteries, as outlined in the following examples.

[0033] As described above, in some embodiments, in addition to hydrotalcite, at least one other type of inorganic particles may be used. Exemplary inorganic particles may include, but are not limited to, inorganic oxides, carbonates, or hydroxides, such as, for example, alumina (e.g., fumed alumina), silica, zirconium oxide, titanium dioxide, mica, boehmite, magnesium hydroxide, calcium carbonate, and mixtures thereof.

[0034] As described above, the polymer films disclosed herein having inorganic particles distributed within a polyolefin matrix and / or coated on one or both of the first and second major surfaces can exhibit in-plane high temperature dimensional stability. In some embodiments, when exposed to 180°C for at least 10 minutes, the polymer film exhibits less than 10% shrinkage in each of the machine direction and the transverse direction. In another embodiment, when exposed to a temperature at least 50°C above the melting point of the polyolefin matrix (or the polyolefin in the polyolefin matrix) for at least 10 minutes, the polymer film exhibits less than 10% shrinkage in each of the machine direction and the transverse direction. In some such embodiments, the coating weight is less than 6 g / m 2 .

[0035] Example 1

[0036] A 9 μm thick microporous ultra high molecular weight polyethylene containing membrane, ENTEK EPX (ENTEK Membranes LLC, OR), was coated with a water-based dispersion containing the following:

[0037]

[0038] The coating dispersion contained 30 wt% solids with a 97 / 3 hydrotalcite / polyvinyl alcohol (PVOH) mass ratio. The membrane was dip coated by a bath containing the aqueous base dispersion, and the thickness of each side of the wet layer was controlled with a No. 7 Mayer rod. The wetted membrane was then dried with a series of air knives and conveyed through a vertical oven at 80°C and wound on a core before testing. Table I shows the physical properties of the coated membrane prepared in Example 1.

[0039] Table I

[0040]

[0041] Example 2

[0042] The naphthenic process oil (140 kg) was distributed into a Ross mixer where the process oil was agitated and degassed. Next, the following items were added and mixed with the oil:

[0043]

[0044] The mixture is blended at about 40°C until a uniform 47w / w% polymer slurry is formed. The polymer slurry is then pumped into a co-rotating twin-screw extruder with a diameter of 103-mm while maintaining a melt temperature of about 215°C. At the same time, hydrotalcite DHT-4V powder (Kasma, USA; Houston, Texas) is added at 5kg / hr using a second loss-in-weight feeder. The extrudate passes through a melt pump, which is fed to a 257-mm diameter annular die with a gap of 2.75mm. The throughput rate through the die is 235kg / hr, and the extrudate is inflated with air to produce a biaxially oriented oil-filled film with a diameter of about 2250mm, and then the inflated extrudate is passed through the upper nip at 20m / min to rupture the bubbles and form a double layer, which is then cut into two separate layers.

[0045] The oil-filled layer was then extracted online with trichloroethylene (TCE) followed by evaporation of the TCE in a hot air oven attached to a series of carbon beds for vapor recovery. The extracted sheet was further stretched in the machine direction (50°C) and transverse direction (128°C) to obtain a 9um thick separator which would become a mother roll.

[0046] The hydrotalcite loading level in the separator was determined to be approximately 4.4 wt % as determined by thermogravimetric analysis.

[0047] Example 3

[0048] Dry mix the following powders:

[0049] 511g HMW-HDPE (molecular weight about 600,000 g / mol)

[0050] 256g fumed alumina (Spectral 81)

[0051] 33g Hydrotalcite DHT-4A-2 (Kaisma, USA)

[0052] The mixed powder and 100g of process oil (Hydrocal 800) are then combined and fed to a 27mm twin-screw extruder. Additional oil is added at the throat of the extruder. The mixture is extruded through a sheet die at an elevated temperature (about 160°C) into a horizontal calender roll stack. The extruded sheet is about 560um thick. The oil-filled sheet is then stretched to 9×9 at 115°C in a Karo-5 laboratory device (Bruckner; Germany). The stretched sheet is then mounted in a frame and extracted with Tergo MCF solvent. The solvent-loaded sheet is retained in a frame and placed in an oven where the solvent is dried at 80°C. The resulting microporous membrane has a thickness of 11.9um, a puncture strength of 294 grams of force, and a Gurley value of 89 (seconds / 100cc air).

[0053] Example 4

[0054] The following example describes a method for titrating hydrotalcite with concentrated HCl. 20 g of hydrotalcite (DHT-4C, Kaisma) was dispersed in 180 g of deionized water. The dispersion was stirred with a magnetic stirring bar throughout the titration. Concentrated HCl (37% HCl, ACS grade, VWR Analysis BHD) was added to a 25 ml burette and used as a titrant. A Milwaukee MW102 pH meter was used to measure the pH during the titration. Initially, a 25 ml burette was used to add concentrated HCl in 0.5 ml increments. The measurement results were recorded after the Milwaukee meter indicated that the pH was stable. The HCl titration curve is shown in Figure 1 These results demonstrate that hydrotalcite has an excellent ability to act as an acid scavenger.

[0055] Example 5

[0056] The impact of hydrotalcite on lithium ion electrolyte aging is assessed as follows. Hydrotalcite (0.54g, DHT-4C, Kaisma) is added to 20ml scintillation vials (borosilicate glass, melamine cap, PTFE seal). The scintillation vials containing hydrotalcite and the control 20ml scintillation vials (not containing hydrotalcite) are dried at 120°C for 48 hours. After drying, the scintillation vials are transferred to a glove box, and 5ml of 1M LiPF6 in 1:1 ethylene carbonate: ethyl methyl carbonate (EC:EMC) electrolyte (Aldrich) is added to each scintillation vial. Then the scintillation vials are sealed and placed in a 60°C baking oven for 144 hours. Figures 2A-2D The 60°C aging results are shown, where Figure 2A The control vial at 0 hours is depicted; Figure 2B A hydrotalcite vial at 0 hours is depicted; Figure 2C depicts a control vial at 144 hours; and Figure 2D The hydrotalcite vial at 144 hours is depicted. As demonstrated, the control vial containing only electrolyte showed significant darkening of the electrolyte ( Figure 2C In contrast, the electrolyte containing hydrotalcite showed minimal discoloration ( Figure 2D ). These results indicate that hydrotalcite works effectively to minimize electrolyte degradation.

[0057] Example 6

[0058] A 9 μm thick microporous ultra-high molecular weight polyethylene containing membrane, ENTEK EPX (ENTEK Membranes, LLC, OR) was coated with a water-based dispersion containing the following:

[0060]

[0061] The coating dispersion consisted of 20 wt% solids with a 45 / 50 / 5 boehmite / hydrotalcite / binder mass ratio. The membrane was dip coated from a bath containing the aqueous base dispersion and the thickness of each side of the wet layer was controlled with a No. 10 Meyer rod. The wetted membrane was then dried with a series of air knives and conveyed through a vertical oven at 80°C and wound on a core prior to testing. Table 2 shows the physical properties of the coated membranes prepared in Example 6.

[0062] Table 2

[0063]

[0064] Example 7

[0065] A 9 μm thick microporous ultra-high molecular weight polyethylene containing membrane, ENTEK EPX (ENTEK Membranes, LLC, OR) was coated with a water-based dispersion containing the following:

[0066]

[0067] The coating dispersion consisted of 20 wt% solids with a 85 / 10 / 5 boehmite / hydrotalcite / binder mass ratio. The membrane was dip coated from a bath containing the aqueous base dispersion and the thickness of each side of the wet layer was controlled with a No. 11 Meyer rod. The wetted membrane was then dried with a series of air knives and conveyed through a vertical oven at 80°C and wound on a core prior to testing. Table 3 shows the physical properties of the coated membranes prepared in Example 7.

[0068] Table 3

[0069]

[0070] It will be apparent to those skilled in the art that many changes may be made to the details of the above embodiments without departing from the basic principles of the disclosure. Therefore, the scope of the disclosure should be determined solely by the following claims.

Claims

1. A freestanding microporous polymer membrane for an energy storage device, the freestanding microporous polymer membrane comprising: A polyolefin substrate having first and second major surfaces, inorganic particles distributed within the polyolefin substrate and / or coated on one or both of the first and second major surfaces, wherein the inorganic particles comprise an acid scavenger.

2. The freestanding microporous polymer membrane of claim 1, wherein: The freestanding microporous polymer membranes exhibit in-plane high temperature dimensional stability.

3. A free-standing microporous polymer membrane as claimed in claim 1 or 2, wherein: These inorganic particles include hydrotalcite.

4. The freestanding microporous polymer membrane of claim 3, wherein: These inorganic particles include synthetic hydrotalcite.

5. The freestanding microporous polymer membrane of claim 1, wherein: These inorganic particles comprise a mixture of hydrotalcite and at least one other type of inorganic particles.

6. The freestanding microporous polymer membrane of claim 5, wherein: These inorganic particles comprise a mixture of about 0.1% to 12% hydrotalcite and about 88% to 99.9% of at least one other type of inorganic particle.

7. A free-standing microporous polymer membrane according to claim 5 or 6, wherein: The at least one other type of inorganic particle comprises an inorganic oxide, carbonate or hydroxide.

8. A freestanding microporous polymer membrane as claimed in any one of claims 1 to 7, wherein: The inorganic particles are distributed throughout the polyolefin matrix.

9. A freestanding microporous polymer membrane as claimed in any one of claims 1 to 8, wherein: The inorganic particles are coated on one or both of the first and second major surfaces.

10. The freestanding microporous polymer membrane according to any one of claims 1 to 9, wherein The freestanding microporous polymeric film exhibits less than 10% shrinkage in each of the machine and transverse directions when exposed to 180°C for at least 10 minutes.

11. A freestanding microporous polymer membrane according to any one of claims 1 to 10, wherein: The inorganic particles are coated on one or both of the first and second major surfaces, and wherein the coating weight is less than 6 g / m 2 .

12. A freestanding microporous polymer membrane as claimed in any one of claims 1 to 11, wherein: The freestanding microporous polymeric membrane exhibits less than 10% shrinkage in each of the machine and transverse directions when exposed to a temperature at least 50°C above the melting point of the polyolefin in the polyolefin matrix for at least 10 minutes.

13. A freestanding microporous polymer membrane according to any one of claims 1 to 12, wherein: Inorganic particles comprising hydrotalcite are distributed throughout the polyolefin matrix, and wherein at least one other type of inorganic particle is coated on one or both of the first and second major surfaces.

14. The freestanding microporous polymer membrane of claim 13, wherein: The at least one other type of inorganic particle comprises an inorganic oxide, carbonate or hydroxide.

15. An energy storage device comprising the free-standing microporous polymer membrane according to any one of claims 1 to 14.

16. A freestanding microporous polymer membrane for an energy storage device, the freestanding microporous polymer membrane comprising: a polyolefin substrate having first and second major surfaces; a coating disposed on one or both of the first and second major surfaces, wherein the coating comprises inorganic particles; and an acid scavenger distributed in at least one of the polyolefin matrix or the coating, wherein the freestanding microporous polymer membrane exhibits in-plane high temperature dimensional stability, and wherein the coating weight is less than 6 g / m 2 .

17. The freestanding microporous polymer membrane of claim 16, wherein: The acid scavenger comprises hydrotalcite.

18. The freestanding microporous polymer membrane of claim 17, wherein: The acid scavenger comprises synthetic hydrotalcite.

19. A freestanding microporous polymer membrane as claimed in any one of claims 16 to 18, wherein: These inorganic particles include inorganic oxides, carbonates or hydroxides.

20. The freestanding microporous polymer membrane of any one of claims 16 to 19, wherein: The freestanding microporous polymeric film exhibits less than 10% shrinkage in each of the machine and transverse directions when exposed to 180°C for at least 10 minutes.

21. A freestanding microporous polymer membrane as claimed in any one of claims 16 to 20, wherein: The freestanding microporous polymeric membrane exhibits less than 10% shrinkage in each of the machine and transverse directions when exposed to a temperature at least 50°C above the melting point of the polyolefin in the polyolefin matrix for at least 10 minutes.

22. A freestanding microporous polymer membrane as claimed in any one of claims 16 to 21, wherein: The acid scavenger is distributed in the polyolefin matrix.

23. A freestanding microporous polymer membrane as claimed in any one of claims 16 to 22, wherein: The acid scavenger is distributed in the coating.

Citation Information

Patent Citations

  • Lithium ion battery

    US10050313B2

  • Acid-scavenging functional separators for power performance of lithium ion electrochemical cells

    US10741812B2

  • Organic / Inorganic Composite Separator Having Morphology Gradient, Manufacturing Method Thereof and Electrochemical Device Containing the Same

    US20080292968A1

  • Organic / inorganic composite microporous membrane and electrochemical device prepared thereby

    US20090111025A1

  • Lithium ion secondary battery

    US7638230B2